2021
DOI: 10.1021/acsphotonics.1c01111
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Emission in the Vicinity of 10 THz due to Auger-Suppressed Recombination of Dirac Fermions in HgCdTe Quantum Wells

Abstract: The discovery of Dirac fermions in a number of 2D and 3D materials boosted the solid-state research in an unprecedented way. Among the many hopes of using their exceptional physical properties, it has been argued that their reduced nonradiative losses would allow graphene to compete with quantum cascade lasers (QCLs) in the race for terahertz (THz) emitters. Unfortunately, the nonradiative Auger recombination (AR) process is still active for massless fermions in gapless graphene. However, for massive Dirac fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 55 publications
0
12
0
2
Order By: Relevance
“…Studies with excitation by a pulsed CO 2 laser did not allow obtaining SE in this structure. On the other hand, it has been experimentally confirmed that SE at wavelength of ∼ 30 µm can be obtained under similar experimental conditions in structures with Auger process threshold of ∼ 20 meV [10]. Note that in both cases the threshold energy is much higher than the lattice temperature 8 K (which corresponds to the energy ∼ 1 meV), which should lead to strong suppression of Auger recombination if the carrier temperature is close to the lattice temperature.…”
Section: Suppression Of Auger Recombination and The Possibility Of Ob...mentioning
confidence: 59%
See 3 more Smart Citations
“…Studies with excitation by a pulsed CO 2 laser did not allow obtaining SE in this structure. On the other hand, it has been experimentally confirmed that SE at wavelength of ∼ 30 µm can be obtained under similar experimental conditions in structures with Auger process threshold of ∼ 20 meV [10]. Note that in both cases the threshold energy is much higher than the lattice temperature 8 K (which corresponds to the energy ∼ 1 meV), which should lead to strong suppression of Auger recombination if the carrier temperature is close to the lattice temperature.…”
Section: Suppression Of Auger Recombination and The Possibility Of Ob...mentioning
confidence: 59%
“…Knowing the QW parameters, one can use numerical methods to estimate the efficiency of Auger recombination, which is one of the main factors hindering the production of long-wavelength SE. As was shown in the works [9,10], the efficiency of Auger recombination correlates with the value of the so-called threshold energy of the Auger process, which is uniquely determined by the band spectrum of the structure under study. The threshold energy is defined as the minimum kinetic energy, in which case a system of three particles can participate in the Auger process [11].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…At the same time, the focus in the studies of such structures shifted to the area of effects caused by the law of dispersion of charge carriers and inversion of bands, in particular, the occurrence of the state of a topological insulator in two-dimensional [7] and three-dimensional structures [8] were shown, the presence of pseudo-relativistic particlesmassless Dirac fermions in massless QWs [9] and Kane fermions in volume CHT films [10][11][12]. CHT-based structures may prove to be a promising material for the creation of detectors and radiation sources in the far and medium infrared range, in particular, for designing of interband lasers [13,14] and for applications in the field of absorption and heterodyne spectroscopy with time resolution in long-wavelength part of the medium IR range (radiation wavelength is 9−30 µm).…”
Section: Introductionmentioning
confidence: 99%